2015
DOI: 10.1016/j.archoralbio.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine promotes Streptococcus mutans extracellular polysaccharide synthesis, cell aggregation and overall lactate dehydrogenase activity

Abstract: Several epidemiology studies have reported a positive relationship between smoking and dental caries. Nicotine, an alkaloid component of tobacco, has been demonstrated to stimulate biofilm formation and metabolic activity of Streptococcus mutans, one of the most important pathogens of dental caries. The first aim of the present study was to explore the possible mechanisms leading to increased biofilm by nicotine treatment from three aspects, extracellular polysaccharides (EPS) synthesis, glucosyltransferase (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 39 publications
4
44
1
Order By: Relevance
“…Studies conducted by Huang et al [18] revealed that nicotine increases the formation of biofilm by the action of SM bacteria, and its metabolic activity on teeth surfaces which suggests the possibility of increased risk of dental caries in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Huang et al [18] revealed that nicotine increases the formation of biofilm by the action of SM bacteria, and its metabolic activity on teeth surfaces which suggests the possibility of increased risk of dental caries in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated a positive relationship between nicotine, the major addictive component of tobacco smoke, and bacterial biofilm formation. For example, Huang et al reported that nicotine could stimulate Streptococcus mutans biofilm formation and its metabolic activity ( Huang et al, 2012 ; Li et al, 2014 ; Huang et al, 2015 ). They also found that nicotine could enhance Streptococcus gordonii biofilm formation, aggregation, and gene expression of binding proteins ( Huang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…An overnight culture of S. mutans was placed in 96-well microtiter plates with TSBS to stimulate S. mutans growth and biofilm formation. Nicotine was added to both study and control groups to increase biofilm formation as this was confirmed in previous studies [5,6,20,25].…”
Section: Discussionmentioning
confidence: 57%
“…A positive correlation has also been found between nicotine and S. mutans biofilm. Nicotine upregulates certain S. mutans virulence genes including GTF and glucan binding protein (GbpA) expression, and Ldh, nlmC, and phosphotransferase system (PTS)-associated genes, which eventually leads to more lactic acid production [5,6]. A recent in-vivo study indicates that caries was higher in Wistar rats infected with S. mutans and treated with nicotine compared with a nicotine-untreated group [7].…”
Section: Introductionmentioning
confidence: 99%